Innovative Learning Management Through Community Identity: A Case Study of The “Kru Rak Thin” Project in Early Childhood Education - Brikshavana, Piyaluck; Seenuan, Thoen; Meesup, Phutcharawalai (Southeast Asia Early Childhood Journal, 2025)
This study examined the development and implementation of an innovative learning management based on community identity within the “Kru Rak Thin” Project for early childhood education in Thailand. The objectives were to (1) investigate local community identities, (2) develop learning innovations based on local community identities, (3) implement these innovations in early childhood classrooms, and (4) reflect on lessons learned. A research and development approach combined with participatory action research was employed across four phases: investigation of community identity, development of a community identity-based learning innovation, classroom implementation, and reflection. Data were collected through interviews, observations, and focus group discussions with community scholars, teachers, and administrators across 29 schools in four provinces. Student teachers identified 26 community identity elements (e.g., Hmong embroidery, traditional weaving, local languages) and developed 31 innovations, including lesson plans, big storybooks, and educational games. Expert evaluations rated 93.5% of these innovations as “good,” while two were “adequate.” Classroom implementation showed that all kindergarten students achieved learning outcomes above 80%. The findings highlight that integrating community identity into early childhood education fosters cultural sustainability, enhances learning achievement, and strengthens collaboration among schools, communities, and future teachers.